Implementation of Agile Governance in Public Administration: A Case Study of Integrated Population Queue System in Bandung Regency - Rachmawati, Emi; Sarihati, Tati (Dinasti Research, 2025)
This study aims to analyse the application of Agile Governance in the Integrated Population Queue System service at the Population and Civil Registry Office of Bandung Regency, specifically through the use of the SAKEDAP application. Since the beginning of 2021, online services have been the main innovation in digitalising population administration services. However, the implementation of this system still faces challenges, especially the Q-Ban restriction that only accommodates 150 queues per day from 4,000 applicants. To overcome these obstacles, strategies such as expanding public information channels, recruiting information technology specialists, and strengthening the capacity of digital systems are needed. The research used a qualitative approach through participatory observation, in-depth interviews, and document analysis, to examine Agile Governance, namely Good Enough Governance, Business Driven, Human Focused, Quick Wins, The application of the Systematic and Adaptive Approach and Simple Design and Continuous Refinement. Beyond that, one additional dimension was found, namely responsiveness as a crucial element in supporting fast and transparent services. Responsiveness is interpreted as the ability of agencies to provide responsive assistance with clear information, thus strengthening the successful implementation of Agile Governance in digital public services that are inclusive and adaptive to community needs.